Radiation Therapy in Hematologic Malignancies An Illustrated Practical Guide - Dabaja, Bouthaina Shbib; Ng, Andrea K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is designed to assist practitioners in managing patients who present with difficult cases of the most common hematological malignancies. The scenarios covered are those that are likely to be encountered in patients with the various forms of Hodgkin$1 (Bs lymphoma, non-Hodgkin$1 (Bs lymphoma, and leukemia. In each of the three sections devoted to these malignancies, multiple cases are presented. The case discussions follow a standard format. A clinical description is followed by a pathological description documenting information relevant to diagnosis and by details of staging work-up, including images. The treatment options are then discussed at length, highlighting relevant literature for each option. Finally, the treatment delivered is identified and images of the planning technique/modality used are provided. This book will be an invaluable aid to decision making for radiation oncologists and will also be of interest for hematologists.s
Part I: Hodgkin$1 (Bs Lymphoma: early stage favourable and unfavourable -- Advanced stage -- Primary refractory -- Relapsed Hodgkin$1 (Bs in the setting of transplant -- Part II: Non Hodgkin$1 (Bs Lymphoma: Diffuse Large Cell Lymphoma -- Early stage -- Advanced stage -- Refractory/palliative -- Follicular lymphoma: Early stage, grade 1,2 -- Advanced stage/palliative -- Extranodal marginal zone: Gastrointestinal origin -- Non-gastrointestinal origin -- Primary mediastinal lymphoma -- Plasmacytoma/multiple myeloma -- Lymphoblastic lymphoma -- Primary CNS lymphoma -- Primary testicular lymphoma -- Mantle cell lymphoma -- Primary skin lymphoma including anaplastic large cell and mycosis fungoides -- Part III: Leukemia: craniospinal irradiation -- treatment of chloromas.s
Keywords: Medicine; Radiotherapy; Hematology; Oncology; Medicine & Public Health; Radiotherapy; Hematology; Oncology